Старообрядцы в Таврической губернии в конце XVII – начале XX в. - Моисеенкова, Л.С. (Материалы по археологии, истории и этнографии Таврии, 1996)
После присоединения Северного Причерноморья и Крыма к России возникла проблема всестороннего освоения этого обширного малозаселенного края. Решалась она путем стихийной народной колонизации и правительственными мерами по переселению различных категорий крестьян из других регионов Российского государства, а также иностранных колонистов, которым предоставлялись значительные льготы. Acording to the Decree (ukaz) of Catherine II from August 26, 1785, Old Believers were granted the permission to settle on the lands between the Dnieper and Perekop. The government gave some privilege, which stimulated the migration of a part of Old Believers to low-developed districts, including Taurida Province. The first migrants from Chernomorsk, Kursk and Novgorod-Seversk provinces settled mainly on the territory of Melitopole and Dnieper districts. During the following decades the area of Old Believers’ settling enlarged. They came to the Crimea. In 1885 there were more than 13,000 Old Believers in Taurida Province, mainly without priests.